TEACHER IN PHYSICAL EDUCATION - Milovan Stamatović; Goran Šekeljić; Žana Bojović; Živorad Marković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The authors of this paper is directed to physical education in elementary school younger and the role of teachers in the implementation of this subject. The first part discusses the importance of physical education for physical and mental development of younger school children of primary school In the second part the authors indicate the quality and organization of physical education in elementary grades, referring to a large number of studies in this field. The third part talks about education and preparing teachers for teaching and learning. Indicated a need for training of teachers in the field of physical education and are given specific proposals.